1′H-Indole-3′-Carbonyl-Thiazole-4-Carboxylic Acid Methyl Ester Blocked Human Glioma Cell Invasion via Aryl Hydrocarbon Receptor's Regulation of Cytoskeletal Contraction. (5th October 2020) - Zhao, Lijiao; Shu, Qiuting; Sun, Hui; Ma, Yunlong; Kang, Dandan; Zhao, Yating; Lu, Jing; Gong, Pei; Yang, Fan; Wan, Fang
Abstract : Blocking glioma cell invasion has been challenging due to cancer cells that can swiftly switch their migration mode, and agents that can block more than one migration mode are sought after. We found that small molecule 2-(1H-indole-3-carbonyl)-thiazole-4-carboxylic acid methyl ester (ITE), an endogenous aryl hydrocarbon receptor (AHR) agonist, can block more than one mode of glioma cell migration, based on cultured cell behavior captured by videos. Data from wound-healing assays and mouse xenograft glioma models corroborated ITE's migration-inhibiting effects while knocking down AHR by siRNA abolished these effects. To identify genes that mediated ITE-AHR's effect, we first collected gene expression changes upon ITE treatment by RNA-seq, then compared them against literature reported migration-related genes in glioma and that were potentially regulated by AHR. MYH9, a component of nonmuscle myosin IIA (NMIIA), was confirmed to be reduced by ITE treatment. When MYH9 was overexpressed in the glioma cells, a good correlation was observed between the expression level and the cell migration ability, determined by wound-healing assay. Correspondingly, overexpression of MYH9 abrogated ITE's migration-inhibiting effects, indicating that ITE-AHR inhibited cell migration via inhibiting MYH9 expression. MYH9 is essential for cell migration in 3D confined space and not a discovered target of AHR; the fact that ITE affects MYH9 via AHR opens a new research and development avenue.